EKSTRAKSI MULTI TAHAP KURKUMIN DARI TEMULAWAK (Curcuma xanthorriza Roxb.) MENGGUNAKAN PELARUT ETANOL (Jurnal Teknik Kimia USU, 2015)
Curcumin is a pigment in turmeric (Curcuma xanthorriza Roxb.), which has an orange-yellow crystal appearance, and commonly being used as a colouring agent. Extraction method which is used in extracting curcumin from turmeric is one stage extraction. This research will study a multi stage extraction of curcumin from turmeric. The purposes of this research is to find the best condition in extracting curcumin using multi stages extraction method to increase the efficiency rate in curcumin extraction. This research used ethanol as a solvent, and effect from variables such as extraction time, solvent concentration, and number of extraction stages are observed. Extraction times are 60 minutes, 120 minutes, and 180 minutes. Variations of ethanol concentration are 50%, 70%, and 96%. Stage numbers of extraction are two stages extraction and three stages extraction. Extracts of curcumin are examined with qualitative analysis and quantitative analysis. The best condition of multi stages curcumin extraction is determined based on yield and content of curcumin. The maximum yield obtained in this study was 16,35 % with conditions 180 minutes extraction time, 96% ethanol concentration, and three stages extraction. The highest content of curcumin obtained is 2,617% with conditions 180 minutes extraction time, 96% ethanol concentration, and three stages extraction. Content means a fraction of yield. These results show that increase in the extraction time, the solvent concentration and the stage numbers of extraction will increase the yield and content of curcumin.